Exploring the Civilizational Approach in Quranic Exegesis - Zahra Mahmudi; Habibollah Babaei (قرآن فرهنگ و تمدن)
The Quran can be analyzed and understood through diverse perspectives, each shaped by distinct intellectual concerns and objectives. This diversity has led to the development of various trends in Quranic exegesis, including the civilizational approach. However, a significant challenge in this field is the lack of precise definitions, theoretical foundations, and systematic methodologies for such approaches. Many exegetes unconsciously embed their personal concerns into their interpretations without explicitly identifying their exegetical framework or adhering to established principles, often resulting in innovative yet unsystematic readings of Quranic verses. This study aims to formalize the civilizational approach by first defining "civilization" and then introducing its principles and methodological foundations. Civilization, as conceptualized here, is a structured, macro-level process that facilitates human development and the flourishing of potentialities through the growth of social relations. In parallel, the civilizational approach to Quranic exegesis offers a comprehensive, systemic, process-oriented, and human-centered framework for engaging with the Quran. By emphasizing key principles—such as the intrinsic relationship between the Quran and civilization and the Quran’s dual dimensions as both a textual guide and an active force—this approach seeks to transform the Quran from a theoretical reference into a dynamic agent that informs practical life and daily interactions.